Aesthetic Transformation in the Production Process of the Augmented Reality Folklore Pasua Realtime Performance - Sri Rustiyanti; Wanda Listiani; Fani Dila Sari; Ida Bagus Gede Surya Peradantha (Institut Seni Indonesia Yogyakarta, 2019)
At present, the view of aesthetics has undergone a shift in line with the aesthetic concepts that have emerged in every era. This aesthetic transformation preserves cultural values in the Millennium Era, following along with the development of performing arts in Indonesia which are also growing. In the production of performing arts there is a need for continuous creativity. Creativity is a very important factor in the life of art, that at least creativity has three benefits: a) enabling humans to provide the strongest response to new situations, b) reacting more strongly to old challenges, c) organizing new situations and giving strong response to it. Creativity allows artists to improve the quality of the presentation of a new and original performance art.This paper is the result of the Research of the Consortium in the field of Art by raising three cultural phenomena that exist in the archipelago, namely Papua, Sunda, and Aceh. The structure of these three territorial territories is a name of virtual reality that is typical of PASUA's Augmented Reality (AR) (Papua-Sunda-Aceh) Performance Arts (PA) 4.0. An augmented reality real time synchronization in the creation of performance art 4.0. which describes the cycle of human life symbolized by the Sun. Beginning with the sun rising in Papua, it then shines on the land of Parahyangan, Sunda and finally sets in Aceh, the Veranda of Mecca.